Sistem Penilaian Angka Kredit Pegawai pada Program Pelatihan Mandiri di BPKP Provinsi Lampung - Dewi Asiah Shofiana; Muhammad Ridho Restu Alam Sobri; Mulia Kesuma Putri (Jurnal Pepadun, 2023)
The Financial and Development Supervisory Agency (BPKP) of Lampung Province routinely holds independent training programs for employees. However, activity data collection is still carried out conventionally which makes it difficult for employees to see the history of the training attended. In fact, these activities have credit numbers that must be recorded carefully because they are related to performance appraisal and have an impact on employee careers. Based on this problem, this research developed a credit scoring information system for self-training programs using a prototyping approach that runs on a web-based platform. The system can provide information about the implementation of independent training activities and employees can make attendance of training activities through the system. Employees can also see the history of the training that has been followed along with the credit score. System testing uses a user acceptance test with a Likert scale which achieves a customer satisfaction index of 92.5%, which shows that it is very satisfying for users and has functioned according to the standards desired by the BPKP of Lampung Province.